Do Targeted R&D Grants Towards Potential Highgrowth Firms Increase Employment and Demand for High Human Capital Workers? - Sven-Olov Daunfeldt; Daniel Halvarsson; Patrik Gustavsson Tingvall; Alexander McKelvie (Institute of Retail Economics (HFI), 2021)
Most previous studies on the employment effects of government R&D grants targeting SMEs are characterized by data-, measurement-, and selection problems, making it difficult to construct a relevant control group of firms that did not receive a R&D grant. We investigate the effects on employment and firm-level demand for high human capital workers of two Swedish programs targeted towards growth-oriented SMEs using Coarsened Exact Matching. Our most striking result is the absence of any statistically significant effects. We find no robust evidence that the targeted R&D grant programs had any positive and statistically significant effects on the number of employees recruited into these SMEs, or that the grants are associated with an increase in the demand for high human capital workers. The lack of statistically significant findings is troublesome considering that government support programs require a positive impact to cover the administrative costs associated with these programs.
Keywords: H81; L25; L26; O38; 330; Innovation policy; R&D grants; Matching grants; Statistical matching methods; High human capital; Firm growth; Outcome additionality